Experiences of peer support for newly qualified nurses in a dedicated online group: Study protocol. (10th April 2019) - Webster, Natalie; Jenkins, Catharine; Oyebode, Jan; Bentham, Peter; Smythe, Analisa
Abstract: Aim: To explore experiences of online peer support for newly qualified nurses. Design: Qualitative study using semi‐structured interviews and thematic analysis. Method: Phase one involves conducting focus groups with newly qualified nurses in the West Midlands area to refine the online peer support environment. Phase two involves 30–40 new nurses joining an online peer group for 3 months; participants will be able to access a general chat community alongside a more structured discussion board. Phase 3 will collect written interview data from all participants about their experiences of online peer support. Face‐to‐face interviews with 10–12 participants will also be undertaken. The study will run from May 2018–October 2019. Findings: Data from focus groups, written and verbal interviews will be analysed using thematic analysis with the aid of NVivo software. Findings will be disseminated to participants and key stakeholders involved in the study and also via publication and networking events. Conclusion: If online peer support is found to be beneficial to new nurses, it may be adopted by local NHS trusts as part of an innovation scheme. Impact: It is important that the psychological well‐being of nurses is addressed as more nurses are now leaving than joining the profession; this is an international concern. Online peer support may offer a sustainable and accessible means of promoting psychological well‐being in the nursing workforce. In such a way, contributory factors to low retention rates such as burnout, stress and job dissatisfaction may also be reduced. 摘要: 目的: 探索支持护士新手的在线同伴经验。 设计: 采用半结构化访谈与主题分析的实证研究 方法: 第一阶段包括在西米德兰兹地区与护士新手建立重点小组, 以完善在线同伴支持环境。第二阶段包括让30‐40名新护士加入一个在线同伴小组, 加入时间为3个月;加入的护士新手将能通过一个更结构化的讨论板来对普通的聊天社区进行访问。第三阶段将对所有参与的护士新手就在线同伴支持经验进行书面访谈的数据收集。还将对10‐12名参与的护士新手进行面谈。本研究将于2018年5月至2019年10月进行。 发现: 通过NVivo软件对重点小组、书面访谈和面谈的数据进行主题分析。研究发现将告知以及通过出版提供给研究的参与者和主要利益相关者。 结论: 如果在线同伴支持被证明对护士新手是有用的, 当地的国家医疗服务信托机构将会对其进行采纳, 从而成为创新计划的一部分。 影响: 重要的是, 随着越来越多的护士选择离职而不是入职, 护士的心理健康问题需要解决, 这是一个国际问题。在线同伴支持可以提供一种持续、容易的方式来促进护士的心理健康。这种方式将会减少导致低员工留存率的因素(倦怠、压力和工作不满等)。